(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
This study aimed at determining the influence of compensation on teachersâ€™ performance in State Secondary School 3 Batusangkar. The method used was a quantitative. The population in this study were all teachers of civil servants in State Secondary School 3 Batusangkar which consist of 43 people. Analyzer used in this research was simple linear regression, coefficient of determinant, and t test. Data processing using SPSS statistics 20 for windows. Based on the results of the study, it was known that simultaneously the compensation has a significant and positive effect on teachersâ€™ performance. The result from simple linear that constant score equal to 100,008 and coefficient score of compensation equal to 0,378 this indicate that there is significant and positive influence to teachersâ€™ performance in State Secondary School 3 Batusangkar. The result of determinant coefficient can be seen that the involvement of compensation variable to teachersâ€™ performance is 17,1%. Result of t-test where t-count > t-table (2,905> 2,701) or sig. <0,01 (0,000 <0,01) which means that Ha is accepted and Ho is rejected. Â Keywords: Compensation, Teachersâ€™ Performance, State Secondary School 3 Batusangkar